Improving farm animal welfare Science and society working together: the Welfare Quality approach - Blokhuis, Harry; Miele, Mara.; Veissier, Isabelle; Jones, Bryan; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers : Imprint: Wageningen Academic Publishers, 2013)
How do you define the quality of life of a farmed animal? This timely book addresses the complex and often controversial issues surrounding the assessment and improvement of farm animal welfare. Based on a large, multi-disciplinary EU funded research project called Welfare Quality, it discusses the relevance of science based welfare assessments and the importance of establishing a fruitful dialogue between science and society. An outline is given of the development of a workable welfare assessment system for cattle, pigs and chickens as well as practical ways of improving the animals' quality of life. This book synthesises the huge body of work carried out by the largest ever international network of scientists and stakeholders in Welfare Quality. It describes some of the obstacles encountered and their solution and why particular paths were chosen. It also clearly sets out what still needs to be done and presents selected strategies and technologies (automation, proxy indicators, targeting of risk factors, etc.) designed to ensure the continued improvement of welfare and its assessment. The book provides a valuable source of knowledge on farm animal welfare for social and animal scientists, students, teachers, policy makers, lobby groups and the animal industry.
Keywords: Life sciences; Life Sciences; Life Sciences, general